PRAGMATIC EQUIVALENCES TRANSLATION STRATEGIES IN ‘DEAR NEMESIS’ WEBTOON MAIN CHARACTER’S UTTERANCES - Muh - Kholiq; Adinda Dhamirah Nur Izzati; Tri Budiarta (SIGEH ELT : Journal of Literature and Linguistics, 2026)
This study explores the pragmatic equivalence of politeness principles in the webtoon Dear Nemesis, examining how Leech’s Politeness Principle and Grice’s pragmatic framework operate in the English Source Language (SL) and their Indonesian Target Language (TL) translations. The research employs a qualitative descriptive method with a pragmatic–translation analysis approach, supported by documentation techniques to collect linguistic data from Chapters 1–7. These chapters were purposefully selected due to their rich occurrences of politeness-maxim expressions and their accessibility as free episodes. The study also applies Newmark’s translation procedures to analyze how politeness strategies are transferred across languages and how translators negotiate meaning to maintain pragmatic equivalence. Findings indicate that, among effective maxims, Tact appears 36 times, Generosity 4, Approbation 31, Modesty 25, Agreement 25, and Sympathy 14. Flouted maxims are also identified, with Tact observed 23 times, Generosity 1, Approbation 37, Modesty 1, Agreement 34, and Sympathy 7. Translation analysis shows that Modulation (56), Transposition (27), and Through Translation (26) are the dominant procedures, followed by Transference (16), Functional Equivalent (16), Reduction (20), and Expansion (14). Overall, the study demonstrates how politeness strategies are expressed, interpreted, and preserved across languages in digital storytelling, offering deeper insights into pragmatic equivalence within webtoon translation.